Estimation of Genetic Parameters of Pinus wallichiana Seedlings in the Nursery - Kaur, Amanpreet; Monga, Rajesh; Bhardwaj, D. R.; Sharma, Jaipal (International Journal of Bio-resource and Stress Management, 2022)
The present study was carried out at the Department of Silviculture and Agroforestry forest nursery, Dr. Y.S. Parmar UHF, Nauni, Solan, HP, India to estimate genetic parameters on seed germination and growth characters of Pinus wallichiana seedlings. Seeds were collected from different altitudinal ranges [1800–2100 (A1), 2100–2400 (A2), 2400–2700 (A3), >2700 (A4) m asl) of Himachal Pradesh in the year 2019–20. The seeds were sown under nursery using randomized block design with three replications. Data recorded for germination and growth character from 10 randomly selected seedlings of each replication and mean data were used for analysis. Analysis of variance revealed that the mean sum of squares were highly significant difference for most of the germination and growth traits. Irrespective of altitudes, the maximum environmental variance was reported in survival percentage (19.2%). The genotypic and phenotypic variance was recorded higher in germination capacity (76.3) and survival percentage (84.9), respectively. Along different altitudinal zones, the genotypic and phenotypic variance was higher at A2 altitude in germination percentage (77.3, 81.3), respectively. Heritability in a broad sense along elevation was more in most of the germination parameters at A2 and growth traits at A1,representing characters are least influenced by environment and selection of character’s is useful. Whereas, the genetic advance was more in germination capacity at A2 altitude indicating the best selection of population from this altitude. So, it would be concluded that seedlings collected from lower (1800–2100m asl)and mid altitudes (2100–2400m asl) were found suitable for large scale plantations in this area.